Evaluation of the Tuberculosis Prevention Program in the Discovery of Tuberculosis Cases in Nosara Public Health Center Palu City - Ashari, Muhammad Rizki; Apriani, Irma; Firmansyah, Firmansyah; Lanyumba, Fitrianty Sutady (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUNDS: Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis. The case in Indonesia rank third with the highest number of TB case in the world. There were 511,873 cases of tuberculosis of all types in 2018. Based on data from the Palu Health Office, the TB cases in Palu in 2018 were still high numbered 557 cases. In 2019, Nosarara Public Health Center had the lowest case finding among the 13 health centers in Palu with 17 TB case findings. The absence of a laboratory in Nosarara Public Health Center for examining sputum samples affected the output in program implementation. AIM: The aim of this study is to evaluate the Control of Tuberculosis in the Discovery of Tuberculosis Cases in Nosarara Public Health Center Palu. MATERIALS AND METHODS: This research used qualitative method with a case study approach. The research informants were 6 people selected through purposive sampling technique. RESULTS: The results summarizes the following : the input aspect in terms of human resources in quantity and quality is inadequate because TB program holders have multiple tasks so that they are not maximal in carrying out their duties and have never attended training, sufficient funds, inadequate facilities and infrastructure, and methods according to guidelines. CONCLUSION: The process of planning, organizing, implementing and supervising has not been maximal, meanwile the output of TB case detection (22%) has not yet reached the predetermined target (80%).It is expected that the Public Health Center will add more health personnel, complete facilities and infrastructure in order to maximize program implementation to achieve predetermined targets.